Selected and Annotated Bibliography for Parents of Preschool-Aged Physically Impaired Children - Schuster, Clara S., Comp. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
Intended for parents of young physically handicapped children, the bibliography lists approximately 70 references on normal development; effects of the disability on family relationships; and on the course, treatment, and prognosis of the disability. Entries are arranged alphabetically by author within each of the three general headings, and information includes title, publisher, date, and a brief annotation. The bibliography is said to be designed to decrease parents' anxiety arising from uncertainty and to increase their sense of competence. (CL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annotated Bibliographies; Child Development; Early Childhood Education; Family Relationship; Infants; Intervention; Parent Role; Physical Disabilities; Student Characteristics; Parent Resources; Reference Materials, Bibliographies